Evaluating AI-generated examination papers in periodontology: a comparative study with human-designed counterparts - Xiang Ma; Wei Pan; Xiao-ning Yu (BMC Medical Education)
Abstract Objective This study systematically evaluates the performance of artificial intelligence (AI)-generated examinations in periodontology education, comparing their quality, student outcomes, and practical applications with those of human-designed examinations. Methods A randomized controlled trial was conducted with 126 undergraduate dental students, who were divided into AI (n = 63) and human (n = 63) test groups. The AI-generated examination was developed using GPT-4, while the human examination was derived from the 2024 institutional final exam. Both assessments covered identical content from Periodontology (5th Edition) and included 90 multiple-choice questions (MCQs) across five formats: A1: Single-sentence best choice; A2: Case summary best choice; A3: Case group best choice; A4: Case chain best choice; X: Multiple correct options. Psychometric properties (reliability, validity, difficulty, discrimination) and student feedback were analyzed using split-half reliability, content coverage analysis, factor analysis, and 5-point Likert scales. Results The AI examination demonstrated superior content coverage (81.3% vs. 72.4%) and significantly higher total scores (79.34 ± 6.93 vs. 73.17 ± 9.57, p = 0.027). However, it showed significantly lower discrimination indices overall (0.35 vs. 0.49, p = 0.004). Both examinations exhibited adequate split-half reliability (AI = 0.81, human = 0.84) and comparable difficulty distributions (AI: easy 40.0%, moderate 46.7%, difficult 13.3%; human: easy 30.0%, moderate 50.0%, difficult 20.0%; p = 0.274). Student feedback revealed significantly lower ratings for the AI test in terms of perceived difficulty appropriateness (3.53 ± 1.03 vs. 4.19 ± 0.76, p < 0.001), knowledge coverage (3.67 ± 0.89 vs. 4.19 ± 0.72, p < 0.001), and learning inspiration (3.79 ± 0.90 vs. 4.25 ± 0.67, p = 0.001). Conclusion While AI-generated examinations improve content breadth and efficiency, their limited clinical contextualization and discrimination constrain their use in high-stakes applications. A hybrid “AI-human collaborative generation” framework, integrating medical knowledge graphs for contextual optimization, is proposed to balance automation with assessment precision. This study provides empirical evidence for the role of AI in enhancing dental education assessment systems.